Իմմոբիլիզացիոն ստրեսը որպես հոգեհուզական սթրեսի մոդել առնետների մոտ - Ն. Ա. Սահակյան (ՀՀ ԳԱԱ հրատ.)
Ուսումնասիրվել է իմմոբիլիզացման ենթարկված առնետների ֆունկցիոնալ իրավիճակը հետստրեսային տարբեր փուլերում: Изучались особенности функционального состояния крыс в динамике постиммобилизационого стресса. Сравнительный анализ результатов, полученных методами МА ВСР у стрессированных крыс, выявил значительные изменения ФС животных. The purpose of this research was to study the peculiarities of functional state of rats in the dynamics of post-immobilization stress. The comparative analysis of the results obtained in stressed rats by methods of MA (mathematical ana¬lysis) VHR detected significant changes in functional state (FS) of animals.
Keywords: Biology; Physiology